Response Of New Sesamol Analogue And Sesamum Indicum Seeds Extract Against Meningitis Triggering Pathogens (Journal of Pharmaceutical Negative Results, 2022)
A certain type of bacteria can cause an upper respiratory tract infection and then travel through the bloodstream to brain and can result in meningitis. Evidence over S. aureus and E. coli to trigger meningitis, antimicrobial potential of Sesamum indicumplant and sesamol intended present study to compare the antimicrobial response of new sesamol analogue (NSA) and Sesamum indicum seeds extract against meningitis triggering pathogens (MTP). Present study involved synthesis of NSA and preparation of sesame seeds extract (SSE). The NSA was characterized using ATR-IR, 1H-NMR and Mass spectrometric data. Both NSA and SSE were tested for antimicrobial potential against MTP, namely: S. aureus and E. coli. Among both, the NSA exhibited much higher antimicrobial potential when compared with SSE. Based on the resultant data present study concludes that NSA possess high inhibition potential against MTP and recommends that NSA should be further evaluated to support its clinical importance.